(untitled) (University Arena, 2025)
Background. The emergence, the development and the affiliation of the Romanian sports structures (such as the Romanian Olympic Committee, the sports federations, the Sports Associations) to similar international organizations have created the favorable framework for the modernization and adaptation of sporting and competitive activity within the sports branches in accordance with international regulation. The training of specialists (coaches, medical doctors, scientific researchers, psychologists etc.) as well as the development of the infrastructure was also targeted, which contributed to the involvement of the Romanian athletes in the European and World Competitions. The Romania’s integration into the systems of international sports competitions took place in the first decades of the 20th century, with its debut at the Summer Olympics in 1924. An important contribution to the affirmation of the Romanian sport at the world level was brought by the representatives of the Romanian sports, elected in the governing structures and in the committees of the international sports organizations. In the following decades of the 20th century, Romania’s international sports exchanges have enjoyed a wide development and diversification, both at sports clubs and at sports federations level, through sports activities organized in the country at all levels of sports and with external correspondence. The involvement of many Romanian cities in the organization of international sports events has also increased. An important contribution of Romania to the promotion of sport in the world was the organization of many European and world competitions, as well as meetings of international sports organizations in all these years. The ’80s and ’90s represent the culmination of Romanian sport, in terms of the active federations and sports clubs, but especially of the impressive number of titles and medals obtained in international sports competitions. Objectives. The paper aims to highlight the participation, involvement and permanent collaboration of all Romanian sports structures in the last century, in order to develop and diversify their relations with international forums, as well as the progress of the Romanian sport on a global level. Methods. The research is an ascertaining type, aiming to highlight Romania’s international evolution in the last century, with emphasis on its results in the representative sports competition: the modern Olympic Games. Results. The international evolution of Romanian sports in the last century is evidenced by the active attendance of this country in the important international competitions, materialized in results that have known both the apogee and the decline, the essential data that contribute to the formation of the history of Romanian sport in this era. Conclusion. Through the constant participation in European, World and Olympic Games championships, but especially through the achievement of remarkable results over time, Romania has become world-renowned as one of the countries with a real sporting potential, the craftsmanship and the record of the athletes making an extraordinary image of the country. At the same time, Romania has proved its constructive vocation in the international sporting life, contributing to the development of sports relations between nations, to the progress of various areas of contemporary sport, to the strengthening of the unity of the international Olympic and sports movement.